Prevalence of Canine Pyometra in Mhow region of Madhya Pradesh - Singh, Durgesh; Vishvakarma, Shashank; Singh Mahour, Sobhran; Shivhare, Madhu; Kumar Bajaj, Nitin (The Indian Journal of Animal Reproduction, 2026)
Pyometra, a serious and potentially fatal uterine infection in intact female dogs, is a common reproductive disorder characterized by the accumulation of purulent material within the uterus. This study aimed to investigate the prevalence of canine from June to November 2024. A total of 1,857 canine cases were presented during the study period, of which 27 cases (1.45%) were diagnosed as pyometra based on clinical signs and ultrasonographic findings. Among 174 recorded gynaecological cases, pyometra accounted for 15.51 per cent cases. The disease was more prevalent in the month of July and August, with the highest incidence observed in Labrador Retrievers (37.03%) and nulliparous females (55.55%). Both open (77.77%) and closed (22.22%) cervix forms of pyometra were identified, with severity classified via ultraso nography. Monthly and breed-wise variation, along with parity status, revealed patterns that may assist in early diagnosis and targeted intervention. The findings highlight the importance of routine reproductive health monitoring in at-risk breeds and non-breeding females. Enhanced diagnostic facilities, including ultrasonography, were crucial for timely detection and management, thereby reducing associated morbidity and mortality.
Keywords: Canine pyometra; Prevalence; Ultrasonography